Software Engineering and Formal Methods 20th International Conference, SEFM 2022, Berlin, Germany, September 26-30, 2022, Proceedings - Schlingloff, Bernd-Holger.; Chai, Ming.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book constitutes the refereed proceedings of the 20th International Conference on Software Engineering and Formal Methods, SEFM 2022, which took place in Berlin, Germany, in September 2022. The 19 full and 3 short papers included in this book were carefully reviewed and selected from 62 submissions. They were organized in topical sections as follows: software verification; program analysis; verifier technology; formal methods for intelligent and learning systems; specification and contracts; program synthesis; temporal logic; and runtime methods. .
Keywords: Software engineering; Data structures (Computer science).; Information theory; Logic programming; 9; Computer systems; Computer programming; Software Engineering; Data Structures and Information Theory; Logic in AI; Control Structures and Microprogramming; Computer System Implementation; Programming Techniques